A performance musical na Folia de Reis de Montes Claros: um estudo etnográfico do Terno João Trindade e do Terno os Peixotinhos - Durães Filho, Geraldo de Alencar (2010)
The term Folia de Reis designates, in Brazil, a variety of cultural events that rememorize, from their performances, the story of the magi visit to Christ Child. This work presents results of a research that contemplated a specific reality of Folia Rite: Montes Claros – city located in northern of Minas Gerais, State of Brazil. In this context, an ethnographic study was realized from the selection of two groups: the Terno João Trindade and the Terno Os Peixotinhos. Considering this Folia universe, this work presents the main musical performance features of these groups, based on the singular aspects of each one, as well as broader dimensions of the cultural context in which they are inserted. The research had as epistemological foundations the ethnomusicology area definitions, particularly in relation to performance studies; and it was build from the following data collection instruments: bibliographic research; documentary research; phonographic research; and participant observation – which covered records audio, video and photos. From analysis and reflections made in this work, it became clear that the “Folia de Reis” is structured around a common theme, but each cultural context presents singular traits in order to structure, valorize and (re)define its performance. With regards to groups investigated, it was clear that their musical performance can only be understood through knowledge on a web of meanings which embraces both the sound elements as other aspects that characterize socially and symbolically the manifestation. In this sense, the establishment of the repertory, the instrumental basis, the lyrics structure and the rhythmic, melodic and harmonic features are interrelated to the dimensions of religious celebrations and a range of other cultural parameters that give life, form and meaning to musical practice of the Folia.